Clinical application of BMP 7 in long bone non-unions - Moghaddam-Alvandi, Arash; Elleser, Charlotte Erika; Biglari, Bahram; Wentzensen, Andreas; Zimmermann, Gerald (Archives of orthopaedic and trauma surgery, 2010)
Non-unions of long bone fractures are a therapeutic and economic problem of increasing frequency. Aside from conservative treatment options such as ultrasound, impulse waves, and casts, the basic surgical options are autogenous cancellous bone grafting, rod dynamization, reamed nailing, plate fixation, and bone transport techniques. If these methods fail to work, there is a need for alternative treatment options.